Audit of the SRIKANDI Information System at the Banten Regional Library and Archives Department using the COBIT 5 Framework - Putri Rizqa Ramadhian; Gagah Dwiki Putra Aryono; Maman Masyhuri (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Digital transformation in the Indonesian government requires reliable and standardized information systems to support quality public services. The Integrated Dynamic Archives Information System (SRIKANDI) is a mandatory archival application for government agencies but faces various technical challenges in implementation. This research aims to evaluate SRIKANDI implementation at the Banten Regional Library and Archives Office using the COBIT 5 framework to identify system maturity levels and areas requiring improvement. The research method uses a quantitative approach with a case study, implementing the COBIT 5 Process Assessment Model (PAM) on EDM01, DSS01, and DSS03 domains through triangulation of observation, interviews, and documentation studies. Research results show the system is at capability level 1 with scores of DSS03 (80%), EDM01 (61.11%), and DSS01 (16.66%), indicating a gap of 2 to achieve target level 3. The study concludes that SRIKANDI has been operational but requires improved documentation, process standardization, and supporting feature implementation to achieve optimal maturity level in supporting digital archival transformation.